PENGUKURAN TINGKAT PELAYANAN KASIR DENGAN PENDEKATAN TEORI ANTRIAN PADA RUMAH MAKAN BKS - Mas'ud, M. Imron (Lembaga Pengembangan Kinerja Dosen, 2021)
The purpose of this study was to determine the average waiting time and average service time in order to provide suggestions for improvements to the queuing system. The data used to analyze this queuing system is primary data in the form of customer arrival time data and service time data for time measurements made using a stopwatch. Our research shows that the inter-arrival interval for arriving customers is between 1.12 and 1.48 minutes. Furthermore, customers spend 13.25 to 19.29 minutes in line and cashiers spend 1.19 to 1.55 minutes serving customers. Based on the results of the three improvement scenarios, the second optimal scenario was chosen, namely the addition of one cashier service facility. Therefore, the current relevant queuing model is a Multichannel-Single Phase queuing system with two queues with two teller services.